The reform of the International System of Units (SI): philosophical, historical, and sociological issues - Courtenay, Nadine de; Darrigol, Olivier; Schlaudt, Oliver (History and philosophy of technoscience, 2019)
Cover; Half Title; Series Page; Title; Copyright; Contents; List of figures and tables; List of contributors; Introduction; 1 The origins of the Metre Convention, the SI and the development of modern metrology; 2 Justifying and motivating an SI for all people for all time; 3 Reforming the International System of Units: on our way to redefine the base units solely from fundamental constants and beyond; 4 Strategies for the definition of a system of units; 5 Relations between units and relations between quantities; 6 On the conceptual nature of the physical constants
Gesehen am 16.10.2020